Letter from George A. Scherpf to James Curtis Booth - Scherpf, George A. (1862)
Request for a copy of a "certain paphlet or rather collection of all the Laws relating to the Mint."
Keywords: Booth, James Curtis, 1810-1888; Mint of the United States; United States Mint